(untitled) (Academic Journal of Internal Affairs, 2023)
Aim: Football is the ‘king’ of the most popular spectator sports. Its popularity has been unbroken since the inception of the sport. Its development has been accompanied by the aspiration of safety. The aims of the examination of the development from a safety technical point of view to show a comprehensive result of the measures and interventions implemented during the process spanning centuries. Methodology: The Authors used both empirical and logical methods in the present research. They take a qualitative approach to the historical development of the safety and security of football matches, looking for correlations between the way in which they are implemented and the means available, through study and content analysis, with a particular focus on contemporary English football. Findings: The safety of the ancient human’s sport is fundamentally different from the sport of XIX and XX centuries, both in terms of the measures and the tools used too. Following the development of football in its current form, after the temporary period of the 1930’s–1950’s, from the end of the 1960’s, the circumstances of English football life became dominant all over the world. After the world wars football was mainly managed on the basis of political and economic principles. Soccer matches, which attract large crowds from different layer of society, became the subject of the passion of spectators with the same interests, supporting a same club, it was the foundation of football hooliganism was formed and reached its summit in the 1980’s. Value: This symptom of fanatics has caused a huge unsolved problem for several participant of society and made it necessary to coordinate the means and measures of securing football matches.